Modern African child and agency for decolonisation in select nigerian novels (2020)
The paper extends beyond the portrayal of Chukwuemeka Ike’s The Bottle Leopard as the postcolonial text which describes the colonialised African society and Chimamanda Adichie’s Purple Hibiscus as feminist text. It interrogates the stronghold of colonial mentality and disillusionment that characterises the Modem African child in the quest for self-assertion and search for identity. Due to the colonial encounter, the indigenous identity of the African child has suffered disapproving retrogression, resulting into lack of confidence in African values. This paper, therefore, argues that the Modem African child today is still a victim of colonialism and remains at a crossroad in the unending search for self- discovery. It submits that the African child has been neglected and foregrounds Ike’s stance that Western education, as well as Adichie’s reflections on effects of Western religion, though part of the development phases of Modem African child, cannot continue to inhibit indigenous African ways of life.